SCR (Selective Catalytic Reduction) catalyst and application

By loading Cu, Co, and metal M onto molecular sieves and controlling the silicon-to-aluminum ratio and the content of active components, the problem of poor low-temperature activity of tightly coupled SCR catalysts was solved, and efficient low-temperature NOx conversion was achieved.

CN121222480APending Publication Date: 2025-12-30WEICHAI POWER CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511126467.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-12
Publication Date
2025-12-30

AI Technical Summary

Technical Problem

Existing tightly coupled SCR catalysts have low NOx conversion efficiency during the low-temperature cold start stage, making it difficult to meet stringent emission limits.

Method used

Cu, Co, and metals M (such as magnesium, barium, strontium, etc.) are supported on molecular sieves to improve the low-temperature NOx conversion performance of the catalyst through synergistic effects. The silica-alumina ratio and the content of active components are controlled to ensure high dispersion and sufficient active sites.

Benefits of technology

It significantly improves the low-temperature NOx conversion performance of copper-based molecular sieve catalysts, achieving efficient nitrogen oxide reduction in the range of 175–550℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005544466220000081
    Figure BDA0005544466220000081
Patent Text Reader

Abstract

The invention relates to the field of catalysts, in particular to an SCR catalyst and application. The SCR catalyst comprises a carrier and an active component loaded on the carrier, the carrier comprises a molecular sieve; the active components comprise Cu, Co and metal M; the metal M comprises at least one of calcium, magnesium, barium, strontium, scandium, titanium, vanadium, chromium, manganese, iron, nickel, zinc, gallium, germanium, yttrium, zirconium, niobium, molybdenum, antimony, tungsten, bismuth, polonium, lanthanum, cerium, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium. According to the SCR catalyst provided by the invention, the active components Cu and Co and the metal M (such as magnesium, barium, strontium, scandium, titanium and the like) are simultaneously loaded on the molecular sieve, and the active component Co and the metal M generate a synergistic effect, so that the low-temperature NOx conversion performance of the copper-based molecular sieve catalyst is greatly improved by combining the active component Co and the metal M.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalysts, and more specifically, to an SCR catalyst and its application. Background Technology

[0002] Currently, the mainstream aftertreatment technology for diesel engines is DOC+DPF+SCR+ASC. However, with increasingly stringent emission regulations, emission limits for pollutants will be further tightened. The current approach is insufficient to meet these emission limits, making tightly coupled SCR (ccSCR) a crucial option. However, existing tightly coupled SCR catalysts exhibit low NOx conversion efficiency during the low-temperature cold start phase.

[0003] Therefore, there is an urgent need to develop SCR catalysts with excellent low-temperature performance. Summary of the Invention

[0004] In view of this, the present invention aims to provide an SCR catalyst and its application, which has excellent low-temperature performance.

[0005] To solve the above-mentioned technical problems, this application is implemented as follows:

[0006] This invention provides an SCR catalyst, the SCR catalyst comprising a support and an active component supported on the support;

[0007] The carrier includes a molecular sieve;

[0008] The active components include Cu, Co, and metal M; the metal M includes at least one of calcium, magnesium, barium, strontium, scandium, titanium, vanadium, chromium, manganese, iron, nickel, zinc, gallium, germanium, yttrium, zirconium, niobium, molybdenum, antimony, tungsten, bismuth, polonium, lanthanum, cerium, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium.

[0009] In some specific embodiments, the molecular sieve includes silicon and aluminum.

[0010] In some specific embodiments, the atomic ratio of silicon to aluminum is (3-200):1.

[0011] In some specific embodiments, the atomic ratio of Cu to Al in the molecular sieve is (0.1 to 0.6):1.

[0012] In some specific embodiments, the molecular sieve has a porous structure.

[0013] Preferably, the pore structure includes micropores, and the pore diameter of the micropores is less than 2 nm.

[0014] In some specific embodiments, the molecular sieve includes at least one of ACO, AEI, AEN, AFN, AFT, AFX, ANA, APC, APD, ATT, BEA, BIK, CDO, CHA, DDR, DFT, EAB, EDI, EPI, ERI, ESV, ETL, FAU, FER, GIS, GOO, IHW, ITE, ITW, LEV, KFI, MER, MFI, MON, MOR, NSI, OWE, PAU, PHI, RHO, RTH, SAT, SAV, SIV, SOD, THO, TSC, UEI, UFI, VNI, YUG, and ZON.

[0015] In some specific embodiments, the molecular sieve includes SSZ-13.

[0016] In some specific implementations, the Cu mass content is >2.0% based on the mass of the molecular sieve.

[0017] In some specific embodiments, the atomic ratio of Co to Cu is (0.01 to 0.9):1.

[0018] In some specific embodiments, the atomic ratio of the metal M to the Cu is (0.01 to 0.9):1.

[0019] A second aspect of the invention also provides an application of an SCR catalyst for the selective catalytic reduction of nitrogen oxides.

[0020] The beneficial technical effects of the present invention through the above technical solution are as follows:

[0021] The SCR catalyst provided by this invention simultaneously supports active components Cu, Co and metal M (such as magnesium, barium, strontium, scandium, titanium, etc.) on a molecular sieve. The active components Co and metal M have a synergistic effect, and the combination of the two greatly improves the low-temperature NOx conversion performance of the copper-based molecular sieve catalyst.

[0022] Other features and advantages of the present invention will be described in detail in the following detailed description section. Detailed Implementation

[0023] This invention discloses an SCR catalyst and its application. Those skilled in the art can refer to this document and appropriately modify the process parameters to achieve the desired result. It is particularly important to note that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.

[0024] In the description of this invention, the list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.

[0025] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0026] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0027] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0028] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0029] With increasingly stringent emission regulations, current routes are struggling to meet emission limits due to further tightening of pollutant emission limits. Closely coupled SCR (ccSCR) routes have become one of the important options for meeting these limits. Closely coupled SCR catalysts need to maintain high NOx conversion efficiency during the low-temperature cold start phase.

[0030] Existing patent CN117258833A discloses a tightly coupled SCR post-treatment composite catalyst, its preparation method, and its application. This invention mixes a metal oxide loaded with noble metal single atoms and a Cu-SSZ-13 molecular sieve, then calcines the mixture to convert the noble metal single atoms into nanoclusters, which are then dispersed on the metal oxide, resulting in the tightly coupled SCR post-treatment composite catalyst. However, this patent uses a mixture of a metal oxide loaded with noble metal single atoms and a copper molecular sieve, which is costly.

[0031] Existing patent CN118804795A discloses an SCR zeolite catalyst for the formation of reduced N2O. This invention discloses a crystalline aluminosilicate microporous zeolite with a maximum ring size of eight tetrahedral atoms, wherein the zeolite comprises: copper, metal M1 (calcium, magnesium, or strontium), and metal M2 (magnesium, calcium, barium, strontium, yttrium, titanium, zirconium, niobium, iron, zinc, silver, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium). After aging at 650℃ for 100 h, the catalyst achieves a maximum NOx conversion efficiency of 66.11% at 175℃. Patent CN118843512A discloses an SCR zeolite catalyst for improved NOx reduction. This invention discloses a crystalline aluminosilicate microporous zeolite with a maximum ring size of eight tetrahedral atoms, comprising copper, manganese, and metals M (magnesium, calcium, barium, strontium, yttrium, titanium, zirconium, niobium, iron, zinc, silver, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium). After aging at 650°C for 100 hours, the catalyst of this patent achieves a maximum NOx conversion efficiency of 70.05% at 175°C under NO-only testing conditions. This means that the catalysts provided in patents CN118804795A and CN118843512A cannot achieve the ideal low-temperature activity.

[0032] In view of this, the present invention provides an SCR catalyst and its application, which exhibits excellent low-temperature activity. The present application and optional embodiments are described in more detail below.

[0033] In some embodiments, the present invention provides an SCR catalyst, the SCR catalyst comprising a support and an active component supported on the support;

[0034] The carrier includes a molecular sieve;

[0035] The active components include Cu, Co, and metal M; the metal M includes at least one of calcium, magnesium, barium, strontium, scandium, titanium, vanadium, chromium, manganese, iron, nickel, zinc, gallium, germanium, yttrium, zirconium, niobium, molybdenum, antimony, tungsten, bismuth, polonium, lanthanum, cerium, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium.

[0036] In this invention, active components Cu and Co and metal M (such as magnesium, barium, strontium, scandium, titanium, etc.) are simultaneously loaded onto a molecular sieve. The active components Co and metal M have a synergistic effect, and the combination of the two greatly improves the low-temperature NOx conversion performance of the copper-based molecular sieve catalyst.

[0037] In this invention, SCR, or Selective Catalytic Reduction, is an effective method for reducing nitrogen oxide (NOx) emissions, primarily applied to waste gas treatment. Its basic principle is to use a catalyst and a reducing agent (such as ammonia) to convert nitrogen oxides in waste gas into harmless nitrogen and water.

[0038] In some embodiments, the molecular sieve comprises silicon and aluminum.

[0039] In some embodiments, the atomic ratio of silicon to aluminum is (3 to 200):1. As an example, the atomic ratio of silicon to aluminum can be any one of 3:1, 5:1, 10:1, 40:1, 50:1, 80:1, 100:1, 140:1, 150:1, 180:1, and 200:1, or a range between any two.

[0040] In this invention, by controlling the atomic ratio of silicon to aluminum in the molecular sieve within the aforementioned range, an optimal balance is achieved between the acid density and hydrothermal stability of the molecular sieve. Simultaneously, sufficient sites are ensured for loading of Cu, Co, and metal M, achieving high dispersion and anchoring of the active components and improving the catalytic activity of the catalyst. If the silicon-to-aluminum ratio is too low, Cu, Co, and metal M will aggregate on the surface of the molecular sieve, reducing dispersion and even clogging the pores; if the silicon-to-aluminum ratio is too high, insufficient ion exchange sites will result in limited loading of the active components, affecting catalytic performance.

[0041] In some embodiments, the molecular sieve has a porous structure.

[0042] In some embodiments, the pore structure includes micropores with a pore size of less than 2 nm.

[0043] In some embodiments, the molecular sieve includes, but is not limited to, at least one of ACO, AEI, AEN, AFN, AFT, AFX, ANA, APC, APD, ATT, BEA, BIK, CDO, CHA, DDR, DFT, EAB, EDI, EPI, ERI, ESV, ETL, FAU, FER, GIS, GOO, IHW, ITE, ITW, LEV, KFI, MER, MFI, MON, MOR, NSI, OWE, PAU, PHI, RHO, RTH, SAT, SAV, SIV, SOD, THO, TSC, UEI, UFI, VNI, YUG, and ZON.

[0044] In some embodiments, the molecular sieve includes, but is not limited to, SSZ-13.

[0045] In some embodiments, the atomic ratio of Cu to Al in the molecular sieve is (0.1 to 0.6):1. As an example, the atomic ratio of Cu to Al in the molecular sieve can be any one of 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, and 0.6:1, or a range between any two.

[0046] In this invention, by controlling the atomic ratio of Cu to aluminum in the molecular sieve within the aforementioned range, sufficient Cu active sites on the molecular sieve can be ensured, preventing Cu overload and aggregation. The synergistic effect of the active component Co and metallic M significantly improves the low-temperature NOx conversion performance.

[0047] In some embodiments, the Cu mass content is >2.0% based on the mass of the molecular sieve. As an example, the Cu mass content based on the mass of the molecular sieve can be any one of 2.5%, 3%, 4%, 5% and 6%, 8% and 10%, 12%, 14%, 15%, 16%, 18% and 20%, or a range between any two.

[0048] In some embodiments, the atomic ratio of Co to Cu is (0.01 to 0.9):1. As an example, the atomic ratio of Co to Cu can be any one of 0.01:1, 0.02:1, 0.04:1, 0.05:1, 0.08:1, 0.1:1, 0.2:1, 0.4:1, 0.5:1, 0.6:1, 0.8:1, and 0.9:1, or a range between any two.

[0049] In some embodiments, the atomic ratio of metal M to Cu is (0.01 to 0.9):1. As an example, the atomic ratio of metal M to Cu can be any one of 0.01:1, 0.02:1, 0.04:1, 0.05:1, 0.08:1, 0.1:1, 0.2:1, 0.4:1, 0.5:1, 0.6:1, 0.8:1, and 0.9:1, or a range between any two.

[0050] In this invention, by controlling the content of active components in the catalyst within the above-mentioned range, and ensuring high activity loading (Cu > 2.0%), the problem of poor low-temperature activity of copper-based molecular sieve catalysts is solved by the precise ratio of Co to metal M, thus achieving both low-temperature performance and long-term stability.

[0051] In this invention, the preparation method of the SCR catalyst can adopt conventional operations known to those skilled in the art, such as hydrothermal synthesis, hydrothermal exchange, ion exchange (e.g., ion co-exchange, stepwise ion exchange), equal-volume impregnation, excess impregnation, rotary evaporation impregnation, and mechanical grinding and mixing.

[0052] A second aspect of the invention also provides an application of an SCR catalyst for the selective catalytic reduction of nitrogen oxides.

[0053] In some embodiments, the temperature at which the SCR catalyst is used for the selective catalytic reduction of nitrogen oxides is 175–550°C. As an example, the temperature at which the SCR catalyst is used for the selective catalytic reduction of nitrogen oxides can be any one of 175°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, and 550°C, or a range between any two.

[0054] The present invention will be further described in detail below through examples. All raw materials used in the examples are commercially available.

[0055] Example 1

[0056] An SCR catalyst, comprising an SSZ-13 molecular sieve support and active components Cu, Co, and Ce supported on SSZ-13, is prepared by a stepwise ion exchange method, including the following steps:

[0057] 19.74 g of cobalt nitrate and 13.02 g of cerium nitrate were dissolved in 500 mL of deionized water. After complete dissolution, 100 g of H-SSZ-13 molecular sieve (Si / Al = 10) was added. The mixture was heated and stirred in a water bath at 60 °C for 12 h. After heating, the mixture was filtered, washed, dried, and calcined to obtain the catalyst Co-Ce-SSZ-13.

[0058] 23.62 g of copper nitrate was dissolved in 500 mL of deionized water. After complete dissolution, the above catalyst was added, and the mixture was heated and stirred in a water bath at 60 °C for 12 h. After heating, the mixture was filtered, washed, dried, and calcined at 600 °C to obtain the SCR catalyst Cu-Co-Ce-SSZ-13. Based on the mass of the molecular sieve, the loading of Cu was 4.1 wt%, the loading of Co was 1.2 wt%, the loading of Ce was 0.8 wt%, the atomic ratio of Co to Cu was 0.31:1, the atomic ratio of Ce to Cu was 0.09:1, and the atomic ratio of Cu to Al in the molecular sieve was 0.3:1.

[0059] Example 2

[0060] An SCR catalyst, comprising a supported SSZ-13 molecular sieve and active components Cu, Co, and La supported on SSZ-13, is prepared by an ion co-exchange method, including the following steps:

[0061] 23.62 g of copper nitrate, 19.74 g of cobalt nitrate, and 12.98 g of lanthanum nitrate were dissolved in 500 mL of deionized water. After complete dissolution, 100 g of H-SSZ-13 molecular sieve (Si / Al = 10) was added, and the mixture was heated and stirred in a water bath at 60 °C for 12 h. After heating, the mixture was filtered, washed, dried, and calcined at 600 °C to obtain the SCR catalyst Cu-Co-La-SSZ-13. Based on the mass of the molecular sieve, the loading of Cu was 3.5 wt%, the loading of Co was 1.5 wt%, the loading of La was 0.6 wt%, the atomic ratio of Co to Cu was 0.46:1, the atomic ratio of La to Cu was 0.08:1, and the atomic ratio of Cu to Al in the molecular sieve was 0.3:1.

[0062] Example 3

[0063] An SCR catalyst, comprising an SSZ-13 molecular sieve support and active components Cu, Co, and Sm supported on SSZ-13, is prepared by a combination of ion exchange and equal-volume impregnation methods, including the following steps:

[0064] 31.40 g of copper sulfate was dissolved in 500 mL of deionized water. After complete dissolution, 100 g of H-SSZ-13 molecular sieve (Si / Al = 10) was added. The mixture was heated and stirred in a water bath at 60 °C for 12 h. After heating, the mixture was filtered, washed, dried, and calcined to obtain the catalyst Cu-SSZ-13.

[0065] 4.94 g of cobalt nitrate and 13.34 g of samarium nitrate were dissolved in a certain amount of water. After complete dissolution, the impregnation solution was slowly added dropwise to the above catalyst, stirred evenly, and allowed to stand at room temperature for 24 h. After drying, calcination at 600 °C, and grinding, the catalyst Cu-Co-Sm-SSZ-13 was obtained. Based on the mass of the molecular sieve, the loading of Cu was 3.9 wt%, the loading of Co was 1.0 wt%, the loading of Sm was 1.5 wt%, the atomic ratio of Co to Cu was 0.28:1, the atomic ratio of Sm to Cu was 0.16:1, and the atomic ratio of Cu to Al in the molecular sieve was 0.3:1.

[0066] Example 4

[0067] An SCR catalyst includes a support SSZ-13 molecular sieve and active components Cu, Co and Zn supported on SSZ-13; the difference from Example 3 is that samarium nitrate is replaced with zinc nitrate, and the amount of zinc nitrate added is 6.82 g, and the rest is the same as in Example 3.

[0068] The final SCR catalyst is Cu-Co-Zn-SSZ-13, in which, based on the mass of the molecular sieve, the loading of Cu is 3.9 wt%, the loading of Co is 1.0 wt%, the loading of Zn is 1.5 wt%, the atomic ratio of Co to Cu is 0.28:1, the atomic ratio of Zn to Cu is 0.38:1, and the atomic ratio of Cu to Al in the molecular sieve is 0.3:1.

[0069] Example 5

[0070] An SCR catalyst includes a support SSZ-13 molecular sieve and active components Cu, Co and Mn supported on SSZ-13; the difference from Example 3 is that samarium nitrate is replaced with manganese nitrate, and the amount of manganese nitrate added is 6.69 g, and the rest is the same as in Example 3.

[0071] The final SCR catalyst is Cu-Co-Mn-SSZ-13, in which, based on the mass of the molecular sieve, the loading of Cu is 3.9 wt%, the loading of Co is 1.0 wt%, the loading of Mn is 1.5 wt%, the atomic ratio of Co to Cu is 0.28:1, the atomic ratio of Mn to Cu is 0.45:1, and the atomic ratio of Cu to Al in the molecular sieve is 0.3:1.

[0072] Example 6

[0073] An SCR catalyst includes an SSZ-13 molecular sieve support and active components Cu, Co and Ca supported on the SSZ-13; the difference from Example 3 is that samarium nitrate is replaced with calcium acetate, and the amount of calcium acetate added is 6.59 g, while the rest is the same as in Example 3.

[0074] The final SCR catalyst is Cu-Co-Ca-SSZ-13, in which, based on the mass of the molecular sieve, the loading of Cu is 3.9 wt%, the loading of Co is 1.0 wt%, the loading of Ca is 1.5 wt%, the atomic ratio of Co to Cu is 0.28:1, the atomic ratio of Ca to Cu is 0.61:1, and the atomic ratio of Cu to Al in the molecular sieve is 0.3:1.

[0075] Example 7

[0076] An SCR catalyst includes a support SSZ-13 molecular sieve and active components Cu, Co and Ca supported on SSZ-13. Unlike Example 3, the molecular sieve used has a silica-alumina ratio of 12, samarium nitrate is replaced with calcium acetate, and the amount of calcium acetate added is 6.59 g. All other aspects are the same as in Example 3.

[0077] The final SCR catalyst is Cu-Co-Ca-SSZ-13, in which, based on the mass of the molecular sieve, the loading of Cu is 3.9 wt%, the loading of Co is 1.0 wt%, the loading of Ca is 1.5 wt%, the atomic ratio of Co to Cu is 0.28:1, the atomic ratio of Ca to Cu is 0.61:1, and the atomic ratio of Cu to Al in the molecular sieve is 0.4:1.

[0078] Comparative Example 1

[0079] An SCR catalyst, differing from Example 3 in that it only involves copper sulfate ion exchange and does not include the subsequent impregnation step; all other steps are the same as in Example 3, specifically including the following steps:

[0080] 31.40 g of copper sulfate was dissolved in 500 mL of deionized water. After complete dissolution, 100 g of H-SSZ-13 molecular sieve (Si / Al = 10) was added, and the mixture was heated and stirred in a water bath at 60 °C for 12 h. After heating, the mixture was filtered, washed, dried, and calcined at 600 °C to obtain the catalyst Cu-SSZ-13. In the final SCR catalyst Cu-SSZ-13, based on the mass of the molecular sieve, the Cu loading was 3.9 wt%, and the atomic ratio of Cu to Al in the molecular sieve was 0.3:1.

[0081] Comparative Example 2

[0082] An SCR catalyst, differing from Example 3 in that only cobalt nitrate was added during impregnation, without the addition of samarium nitrate; otherwise, it was identical to Example 3. In the final SCR catalyst Cu-Co-SSZ-13, based on the mass of the molecular sieve, the Cu loading was 3.9 wt%, the Co loading was 1.0 wt%, the atomic ratio of Co to Cu was 0.28:1, and the atomic ratio of Cu to Al in the molecular sieve was 0.3:1.

[0083] Comparative Example 3

[0084] An SCR catalyst differs from Example 3 in that the amount of copper sulfate added during ion exchange is 7.85 g, while all other aspects are the same as in Example 3. In the final SCR catalyst Cu-Co-Sm-SSZ-13, based on the mass of the molecular sieve, the loading of Cu is 0.9 wt%, the loading of Co is 1.0 wt%, the loading of Sm is 1.5 wt%, the atomic ratio of Co to Cu is 1.21:1, the atomic ratio of Sm to Cu is 0.71:1, and the atomic ratio of Cu to Al in the molecular sieve is 0.07:1.

[0085] Test case

[0086] The SCR catalysts prepared in the examples and comparative examples were subjected to hydrothermal aging and performance testing, and the NOx conversion efficiency at 175℃, 200℃, 250℃, and 300℃ was calculated. The aging conditions were 750℃ for 12 h with 10% H2O, and the testing conditions were a reaction space velocity of 200,000 h⁻¹. -1 The test gas composition was: [NO] = 500 ppm, [NH3] = 550 ppm, [O2] = 5%, with nitrogen as the balance gas. The NOx conversion efficiency test results are shown in Table 1.

[0087] Table 1. NOx Conversion Efficiency Test Results

[0088]

[0089] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. An SCR catalyst, characterized by, The SCR catalyst comprises a carrier and an active component supported on the carrier; The carrier comprises a molecular sieve; The active component comprises Cu, Co and a metal M; the metal M comprises at least one of calcium, magnesium, barium, strontium, scandium, titanium, vanadium, chromium, manganese, iron, nickel, zinc, gallium, germanium, yttrium, zirconium, niobium, molybdenum, antimony, tungsten, bismuth, polonium, lanthanum, cerium, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium.

2. The SCR catalyst according to claim 1, characterized in that The molecular sieve comprises silicon and aluminum; The atomic ratio of the silicon to the aluminum is (3-200):

1.

3. The SCR catalyst according to claim 2, characterized in that The atomic ratio of the Cu to Al in the molecular sieve is (0.1-0.6):

1.

4. The SCR catalyst of claim 1, wherein, The molecular sieve has a pore structure; The pore structure comprises micropores, and the micropores have a pore diameter less than 2nm.

5. The SCR catalyst of claim 1, wherein, The molecular sieve comprises at least one of ACO, AEI, AEN, AFN, AFT, AFX, ANA, APC, APD, ATT, BEA, BIK, CDO, CHA, DDR, DFT, EAB, EDI, EPI, ERI, ESV, ETL, FAU, FER, GIS, GOO, IHW, ITE, ITW, LEV, KFI, MER, MFI, MON, MOR, NSI, OWE, PAU, PHI, RHO, RTH, SAT, SAV, SIV, SOD, THO, TSC, UEI, UFI, VNI, YUG and ZON.

6. The SCR catalyst according to claim 5, characterized in that The molecular sieve comprises SSZ-13.

7. The SCR catalyst of claim 1, wherein, The mass content of Cu is >2.0% based on the mass of the molecular sieve.

8. The SCR catalyst of claim 1, wherein, The atomic ratio of the Co to Cu is (0.01-0.9):

1.

9. The SCR catalyst of claim 1, wherein, The atomic ratio of the metal M to Cu is (0.01-0.9):

1.

10. Use of an SCR catalyst according to any one of claims 1 to 9, characterized in that The SCR catalyst is used for selective catalytic reduction of nitrogen oxides.

Citation Information

Patent Citations

  • SCR zeolite catalyst for reduced N2O formation

    CN118804795A

  • SCR zeolite catalyst for improved NOx reduction

    CN118843512A